2010
DOI: 10.1080/19378629.2010.519773
|View full text |Cite
|
Sign up to set email alerts
|

A “knowledge profile” of an engineering occupation: temporal patterns in the use of engineering knowledge

Abstract: The following( APA) citation may be used to reference this manuscript:Gainsburg, J., Rodriguez-Lluesma, C., Bailey, D. (2010). A "knowledge profile" of an engineering occupation: temporal patterns in the use of engineering knowledge. Retrieved from http://scholarworks.csun.edu Citation: Gainsburg, J., Rodriguez-Lluesma, C., Bailey, D. (2010). A "knowledge profile" of an engineering occupation: temporal patterns in the use of engineering knowledge.Engineering Studies, 2:3, 10.1080/19378629.2010.519773 This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 11 publications
0
29
0
1
Order By: Relevance
“…Many reactions have challenged the claim of domestication. Gainsburg et al (2010) found that workplace knowledge and commitments in an engineering occupation may derive more from on-the-job experience than from prior formal education. Studies based in the United Kingdom have wrestled with such issues as employer scorn for formal engineering education, relative disinterest by government agencies, tension over the continuing role of craft training, and workers managing dual commitments inside and outside of industrial organizations.…”
Section: For Private Industry?mentioning
confidence: 99%
“…Many reactions have challenged the claim of domestication. Gainsburg et al (2010) found that workplace knowledge and commitments in an engineering occupation may derive more from on-the-job experience than from prior formal education. Studies based in the United Kingdom have wrestled with such issues as employer scorn for formal engineering education, relative disinterest by government agencies, tension over the continuing role of craft training, and workers managing dual commitments inside and outside of industrial organizations.…”
Section: For Private Industry?mentioning
confidence: 99%
“…Dym and colleagues briefly describe and point to research on several languages that are used to represent engineering and design knowledge; among these representations are verbal or textual statements (Dym, Agogino, Eris, Frey, & Leifer, 2005). Other investigations of professional engineers' use of mathematics have examined how they employ mathematical representations in their work (Gainsburg, 2007;Gainsburg, Rodriguez-Lluesma, & Bailey, 2010). All these works demonstrate that engineering students and professionals must flexibly use multiple formal and informal representational systems to problem solve and design effectively.…”
Section: Background Representationsmentioning
confidence: 99%
“…The role of technical considerations in design is made visible in several studies on engineering design. For example, an ethnographic study by Gainsburg, RodriguezLluesma, and Bailey discusses how structural engineers regularly employ "considerable numbers of theoretical tools covering a broad spectrum of topics" (p. 206) 28 among several forms of knowledge. And while Buciarrelli's work is well-known for richly describing engineering design as a "social process", his ethnographic research also shows how practicing engineers consciously utilize knowledge from their respective technical "object worlds," or realms of instrumental thinking where abstraction, reductionism, and quantification are predominant.…”
Section: Technical Considerationsmentioning
confidence: 99%
“…When non-technical elements are viewed as constraints, the information sought about such elements tends to be quantifiable. 27,28 This category can also include non-technical constraints related to the process by which a system or artifact is designed, e.g., team schedules, travel logistics, etc. Inclusion of such considerations reflects the fuzzy boundary between the design itself and the "social process" of design.…”
Section: Non-technical Constraintsmentioning
confidence: 99%